2019
DOI: 10.1002/jor.24529
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Signature for Non‐Responders to Total Joint Replacement Surgery in Primary Osteoarthritis Patients: The Newfoundland Osteoarthritis Study

Abstract: Although total joint replacement (TJR) surgery is considered as the most effective treatment for advanced osteoarthritis (OA) patients, up to one‐third of patients reported unfavorable long‐term post‐operative pain outcomes. We aimed to identify metabolic biomarkers to predict non‐responders to TJR using a metabolomics approach. TJR patients were recruited and followed‐up at least 1‐year post‐surgery; TJR outcomes were assessed by Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…Metabolic profiling was performed on plasma as per our previous study (Costello et al 2019) using a commercially available generic metabolomic assay kit-the Biocrates AbsoluteIDQ p180 commercial kit (BIOCRATES Life Sciences AG, Innsbruck, Austria) which assesses 186 metabolites, including acylcarnitines, amino acids, biogenic amines, glycerophospholipids, monosaccharides, and sphingolipids. The full list of the metabolites is provided in Supplementary Table 1.…”
Section: Metabolic Profiling and Statistical Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Metabolic profiling was performed on plasma as per our previous study (Costello et al 2019) using a commercially available generic metabolomic assay kit-the Biocrates AbsoluteIDQ p180 commercial kit (BIOCRATES Life Sciences AG, Innsbruck, Austria) which assesses 186 metabolites, including acylcarnitines, amino acids, biogenic amines, glycerophospholipids, monosaccharides, and sphingolipids. The full list of the metabolites is provided in Supplementary Table 1.…”
Section: Metabolic Profiling and Statistical Methodsmentioning
confidence: 99%
“…Participants were recruited from those undergoing TJR in St. John's, Newfoundland and Labrador (NL), Canada (Costello et al 2019). Diagnosis was made as per the American College of Rheumatology clinical diagnostic criteria (Altman et al 1991) and confirmed using pathology reports postsurgery.…”
Section: Study Participantsmentioning
confidence: 99%
See 3 more Smart Citations